Evaluation of patient related modifiable and non-modifiable risk factors in causation of surgical site infection in various abdominal surgeries - Agrawal, Abhinav; Madeshiya, Shivam; Khan, Roshni; Tripathi, Shashank S.; Bharadwaj, Gaurav (International Surgery Journal, 2018)
Background: Surgical Site Infection (SSI) is second commonest nosocomial complication in surgical speciality. Majority of surgical wounds are contaminated by microbes, but in most cases, infection does not develop because innate host defense are quite efficient in elimination of contaminants. The objective of this study was to evaluate patient related risk factors in causation of surgical site infection in various abdominal surgeries. Methods: All patients who admitted in surgical OPD/emergency and undergoing abdominal surgical procedures were included in study. This observational study was comprised of 952 subjects. Patients were observed in wards and during follow up to assess signs and symptoms of surgical site infection. Results: Result were analysed in terms of age, sex, distribution of cases based on case scenario (elective v/s emergency), wound class, type of surgery (laparoscopic v/s open), smoking, diabetes, duration of surgery, complete hemogram before and after blood transfusion, number of blood transfusions, albumin, blood sugar level, discharge from surgical site, number of days of drains, stoma and hospital stay. Conclusions: Surgical site infection in emergency cases were found to be higher as compared to elective cases. Occurrence of SSI proportionately increased with degree of contamination, duration of surgery and age of patients. Laparoscopic procedures showed fewer incidences of surgical site infection as compared to open procedures. Various factors showed statistically significant association with surgical site infections were diabetes, smoking, blood transfusions, haemoglobin and albumin levels. Presence of stomas and drains were associated with increased incidence of SSI but could not be proven statistically.